Sentence structure in the works of J. Arbes, A. Jirásek, and J. Zeyer - Schacherl, Martin (Bohemistyka, 2022)
The aim of this study is to analyse and compare the use of the sentences in the selected texts by Jakub Arbes, Alois Jirásek and Julius Zeyer. On the basis of a set of frequency analyses, the contribution summarizes selected individual aspects of the prose style used in the works of Jakub Arbes, Alois Jirásek, and Julius Zeyer. The paper deals with linear sentence length of simple sentences and commplex/compound sentences in texts of the selected authors. The focus is on characteristic features of the narrative style of these very much different 19th Century Czech Authors as well as on similarities relating their style.